Pengaruh Sarana dan Prasarana Serta Pelayanan Publik Terhadap Kepuasan Masyarakat: Indonesia - Imam Firdaus; Riny Viri Insy; Zulaili Zulaili; Nuraini Nuraini (Jurnal Bisnis, Manajemen, dan Ekonomi, 2023)
Given the lack of importance of the influence of facilities and infrastructure on community satisfaction, village officials must further improve existing facilities and infrastructure in the village so that people are satisfied with existing facilities. Village Governments and City Governments should focus more on improving the quality of services through the completeness of facilities and infrastructure. The purpose of this study was to reveal the facilities and infrastructure both partially and simultaneously which have a strong influence on community satisfaction in Durian Village, Pantai Labu District, Deli Serdang Regency and to find out what the percentage is. The method used in this study is a quantitative approach, while the variables studied are facilities and infrastructure (X1), public services (X2) and community satisfaction (Y). The population that the author examined was all the people in Durian Village, Pantai pumpkin District, Deli Serdang Regency. According to data from employees who work there, the population is 4300 people. So the sample used in this study was 98 people. The technique used uses sampling with accidental techniques. The variables of facilities and infrastructure (X1) and public services (X2) are able to contribute to the influence of the community satisfaction variable by 15.2% while the remaining 84.8% is influenced by other variables not examined in this study. From the conclusions above, the authors provide suggestions considering the lack of significance of the effect of the facilities and infrastructure variables on community satisfaction, the village apparatus must further improve the existing facilities and infrastructure in the village so that the community feels satisfied with the facilities and infrastructure they have. The Village Government and City Government should focus more on improve service quality through complete facilities and infrastructure